Superparamagnetism in MgO-based magnetic tunnel junctions with a thin pinned ferromagnetic electrode - COEY, JOHN; FENG, JIA-FENG; VENKATESAN, MUNUSWAMY (My University, 2010)
MgO-based magnetic tunnel junctions have been fabricated with a thin Co40Fe40B20 (CoFeB) layer in the pinned synthetic antiferromagnetic CoFe/Ru/CoFeB stack. An inverted tunneling magnetoresistance is observed due to the unbalanced synthetic antiferromagnet. Superparamagnetic nanoparticles form when the CoFeB layer is thinner than 1.5 nm, and an abnormal temperature dependence of the junction resistance is associated with superparamagnetism when the thermal fluctuation energy exceeds the magnetic anisotropy energy. This explanation accounts for the temperature dependence of the tunneling magnetoresistance effect.
PUBLISHED
Keywords: Physics; thin films; Nanoscience & Materials